THE EFFECT OF SERVICE QUALITY ON INDIHOME CUSTOMER SATISFACTION AT PT. TELKOM AKSES MALANG - Bagus Setiawan; Adelia Rahma; Ery Tri Djatmika Rudijanto Wahju Wardhana; Puji Handayati; Mohammad Rofiudin; Achmad Barizi (International Journal of Economics and Management Research, 2022)
This study aims to determine the effect of Service Quality on Indihome Customer Satisfaction at PT. Telkom Access Malang, and how much influence the Service has on Indihome Customer Satisfaction at PT. Telkom Access Malang. The factor tested in this study is service quality as an independent variable. While customer satisfaction as the dependent variable. The research method used in this research is a quantitative descriptive method. The population in this study are IndiHome Malang provider customers. The sampling technique used in this study was purposive sampling, where the sample was selected based on certain considerations with a sample size of 100 people. While the analytical method used in this study is linear and multiple regression analysis at a significance level of 5%. The program used in analyzing the data uses the Statistical Package for Social Sciences (SPSS) Ver. 18.00. The test results show that physical evidence, reliability, responsiveness, assurance and empathy partially and simultaneously have a significant effect on customer satisfaction of IndiHome Malang Providers. The results showed that service quality including physical evidence, reliability, responsiveness, assurance and empathy had an influence on customer loyalty, meaning that to maintain customer loyalty one must pay attention to the 5 service quality factors, one must determine the concept of good service, for example trying to meet needs and wants as well as provide convenience for consumers who enjoy the service. Customer satisfaction with services is the key to success, not only in the short term, but sustainable excellence